PENGARUH YESTERDAY OPEN DAN CLOSE PRICE TERHADAP TODAY OPEN PRICE DENGAN MEMANFAATKAN PIVOT LEVEL UNTUK MEMPREDIKSI PERGERAKAN VALUTA ASING - Effendy, M. Yusuf (Jurnal Manajemen Magister Darmajaya, 2016)
Online foreign exchange trading requires in-depth analysis and accurate. One of the techniques is technical analysis to determine the levels of support and resistance which will be able to withstand the movement of currency exchange rates. Among these is the popular use of pivot level. The questions, which level forms support and resistance? Is there any correlation among Yesterday Open Price, Yesterday Close Price and Today Open Price to the formation of support and resistance? Using historical data of currency exchange rate movements almost last 20 years, this is a descriptive and quantitative research approaches. The study examines correlation among Yesterday Open Price, Yesterday Close Price and Today Open Price relative with its position to pivot point, to determine the areas which serve as resistance and support. The research uses Structural Equation Model (SEM) method with Path Analysis approach. The research affirmed that there are significant correlations between Yesterday Close Price and Today Open Price on determination of resistance and support area. This research can be used as a basis for developing Decision Support System in term of Expert Advisor for online forex trading.Â Keyword: Yesterday Open, Close Price., Today Open Price, Pivot Level, Forex Online Trading